Macroeconomic Perspective on the Growth of Corporate Sharia Bonds (Sukuk) in Indonesia - Erna Apriani; Dian Rachmawati Afandi; Abdul Latif; Aprilianti (Universitas Airlangga, 2023)
ABSTRACT This study aimed to examine macroeconomic factors such as economic growth, inflation, money supply, unemployment rate, and world oil prices as moderating variables on the growth of corporate Islamic bonds (sukuk) in Indonesia. The method of analysis in this research was quantitative causality with an analytical approach. The analysis technique used was a moderation regression model. The sample in this study was the growth of corporate Islamic bonds (sukuk) for the last ten years, from 2013 to 2022, in monthly data. The results showed that the growth of Sukuk was partially affected by the variables of inflation, money supply, and unemployment. However, the GDP variable does not affect the growth of Sukuk. The moderating variable of world oil prices can moderate the variables of GDP, money supply, and unemployment rate on the growth of Sukuk, but does not moderate the variable of inflation on the growth of Sukuk. The results of this study can be used as an academic reference and information for issuers and potential investors in making investment decisions from macroeconomic factors that have been studied such as inflation, money supply, unemployment rate, and world oil prices. Keywords: Gross Domestic Product, Macroeconomics, Unemployment Rate, Corporate Sukuk ABSTRAK Penelitian ini bertujuan untuk mengetahui faktor-faktor makroekonomi seperti pertumbuhan ekonomi, inflasi, uang beredar, tingkat pengangguran, dan harga minyak dunia sebagai variabel moderasi pada pertumbuhan obligasi syariah (sukuk) korporasi di Indonesia. Metode analisis pada penelitian ini ialah kuantitatif kausalitas dengan pendekatan analitik. Teknik analisis yang dipakai menggunakan model regresi moderasi. Sampel penelitian ini ialah pertumbuhan obligasi syariah (sukuk) korporasi sepuluh tahun terakhir, dari tahun 2013 sampai dengan 2022 dalam data bulanan. Hasil penelitian menunjukan secara parsial variabel inflasi, uang beredar, dan tingkat pengangguran mempengaruhi pertumbuhan sukuk, namun berbeda dengan variabel GDP tidak mempengaruhi pertumbuhan sukuk. Variabel moderasi harga minyak dunia mampu memoderasi variabel GDP, uang beredar, dan tingkat pengangguran pada pertumbuhan sukuk, namun tidak memoderasi variabel inflasi pada pertumbuhan sukuk. Hasil penelitian ini dapat dipakai sebagai refrensi akdemisi, dan informasi bagi perusahaan penerbit serta para calon investor dalam menentukan keputusan investasi dari faktor makroekonomi yang telah diteliti seperti inflasi, uang beredar, tingkat pengangguran, dan harga minyak dunia. Kata kunci: Gross Domestic Product, Makro Ekonomi, Tingkat Pengangguran, Sukuk Korporasi